2020
DOI: 10.1016/j.jinteco.2020.103308
|View full text |Cite
|
Sign up to set email alerts
|

Inflation targeting as a shock absorber

Abstract: We study the characteristics of inflation targeting as a shock absorber, using quarterly data for a large panel of countries. To overcome an endogeneity problem between monetary regimes and the likelihood of crises, we propose to study large natural disasters. We find that inflation targeting improves macroeconomic performance following such exogenous shocks. It lowers inflation, raises output growth, and reduces inflation and growth variability compared to alternative monetary regimes. This performance is mos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
19
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(23 citation statements)
references
References 63 publications
3
19
0
1
Order By: Relevance
“…The usual transmission mechanism cited in the literature works through inflation expectations (Ball and Sheridan, 2004;Vega and Winkelried, 2005;Gürkaynak et al, 2007;Batini and Laxton, 2007;Svensson, 2009;Lin and Ye, 2009;Miao, 2009;Walsh, 2009;Revenna, 2010;Ball, 2011;Tillmann, 6 For studies that propose a similar idea without a formal hypothesis test, see Mishkin and Posen (1997), Corbo et al (2002), andBernanke et al, (2018). Fratzscher et al (2020) find that economies with IT regimes show lower inflation rates after a large natural disaster compared with economies with alternative monetary regimes. Angeriz and Arestis (2008) provide empirical evidence that suggests that both ITCBs and (two) non-ITCBs are equally successful in locking in low inflation rates using intervention analysis to multivariate structural time series models.…”
Section: Hypothesis and Theoretical Frameworkmentioning
confidence: 85%
“…The usual transmission mechanism cited in the literature works through inflation expectations (Ball and Sheridan, 2004;Vega and Winkelried, 2005;Gürkaynak et al, 2007;Batini and Laxton, 2007;Svensson, 2009;Lin and Ye, 2009;Miao, 2009;Walsh, 2009;Revenna, 2010;Ball, 2011;Tillmann, 6 For studies that propose a similar idea without a formal hypothesis test, see Mishkin and Posen (1997), Corbo et al (2002), andBernanke et al, (2018). Fratzscher et al (2020) find that economies with IT regimes show lower inflation rates after a large natural disaster compared with economies with alternative monetary regimes. Angeriz and Arestis (2008) provide empirical evidence that suggests that both ITCBs and (two) non-ITCBs are equally successful in locking in low inflation rates using intervention analysis to multivariate structural time series models.…”
Section: Hypothesis and Theoretical Frameworkmentioning
confidence: 85%
“…We follow the literature on the macroeconomic effects of natural disasters (Noy, 2009;Noy and Nualsri, 2011;Parker, 2018 andFratzscher et al, 2020) and use the reported estimated damage as our disaster variable. This measure captures the direct damage to crops, property and livestock, measured in US dollars and valued at the moment of the event.…”
Section: Datamentioning
confidence: 99%
“…This measure captures the direct damage to crops, property and livestock, measured in US dollars and valued at the moment of the event. As the effects of the disasters on inflation depend on the size of the disaster and to standardise across countries, we follow Fratzscher et al (2020) and divide the estimated damage by the level of monthly current-price GDP in the affected country, 12 months prior to the event. In consequence, our disaster variable captures the estimated monetary damage of the event in percent of GDP.…”
Section: Datamentioning
confidence: 99%
“…A decade after Hamond's (2012) work, inflation targeting has been described in differing lights by many stakeholders. Fratzscher et al (2020) describe inflation targeting as a shock absorber that protects the economy from perturbations and vulnerabilities. Ekinci et al (2020) found that inflation targeting had positive effects on economic growth on many countries in their sample.…”
Section: Literature Reviewmentioning
confidence: 99%